Biomechanical Comparison of Self-Compressing Screws and Cortical Screw Inserted with Lag Fashion in Canine Cadaveric Humeral Condylar Fracture Model - Jun-sik Cho; Jung Moon Kim; Youn-woo Choo; Jooyoung Kim; Sorin Kim; Hwi-yool Kim (Veterinary Sciences)
This study compares the compression force of cortical screws used in lag fashion with partially threaded cannulated screws and fully threaded headless cannulated screws as fixation methods for humeral condylar fractures in dogs. Cadavers of eleven dogs weighing an average of 10.99 ± 2.51 kg (6.1–14.4 kg) were used. The humeri were subjected to simulated fracture by performing an osteotomy at the trochlea of humerus and classified into three groups: Group 1 applied a 3.0 mm cortical screw applied in a lag fashion, Group 2 applied a 3.0 mm partially threaded cannulated screw, and Group 3 applied a 3.5 mm fully threaded headless cannulated screw. The samples were then placed in a material testing machine, and a compression force was applied vertically to the lateral condyle until failure. There were statistically significant differences in failure load between the groups (p = 0.009). The maximum failure load in Group 3 was significantly higher than in Group 2 (p = 0.014), while there were no statistically significant differences between Group 1 and Group 2) or between Group 1 and Group 3. Partially threaded cannulated screws and fully threaded headless cannulated screws can be alternatives to traditional stabilization methods, offering simpler procedures and additional advantages.